Photocatalytic decomposition of N2O over g-C3N4/WO3 photocatalysts - Reli, Martin; Svoboda, Ladislav; Šihor, Marcel; Troppová, Ivana; Pavlovský, Jiří; Praus, Petr; Kočí, Kamila (Environmental science and pollution research international, 2018)
Although the nitrous oxide belongs among three of the most contributing greenhouse gases to global warming, it is quite neglected by photocatalytic society. The g-C3N4 and WO3 composites were therefore tested for the photocatalytic decomposition of N2O for the first time. The pure photocatalysts were prepared by simple calcination of precursors, and the composites were prepared by mixing of suspension of pure components in water followed by calcination. The structural (X-ray diffraction, X-ray photoelectron spectroscopy, high-resolution transmission electron microscopy), textural (N2 physisorption), and optical properties (diffuse reflectance spectroscopy, photoluminescence spectroscopy, photoelectrochemical measurements) of all composites were correlated with photocatalytic activity. The experimental results and results from characterization techniques confirmed creation of Z-scheme in the WO3/g-C3N4 composites, which was confirmed by hydroxyl radicals' trapping measurements. The photocatalytic decomposition of N2O was carried out in the presence of UVA light (peak intensity at 365 nm) and the 1:2 WO3/g-C3N4 composite was the most active one, but the photocatalytic activity was just negligibly higher than that of pure WO3. This is caused by relatively weak interaction between WO3 and g-C3N4 which was revealed from XPS.
Keywords: wolfram; fotoelektronová spektroskopie; OH trapping; katalýza; oxid dusičitý; Photoelectron Spectroscopy; Light; Tungsten; světlo; Hydroxyl Radical; hydroxylový radikál; Catalysis; X-Ray Diffraction; Photocatalysis; transmisní elektronová mikroskopie; N2O decomposition; Photochemical Processes; fotochemické procesy; chemické modely; Heterojunction; Nitrogen Dioxide; Microscopy, Electron, Transmission; g-C3N4; Models, Chemical; difrakce rentgenového záření; WO3